NEUROLOGIC OUTCOME AFTER INTRANEURAL AND PERINEURAL SCIATIC NERVE BLOCK IN PIGS - Eldan Kapur; Ilvana Hasanbegović-Vučković; Maida Šahinović; Amela Kulenović; Almira Lujinović (Veterinaria, 2013)
Studies in animals have suggested that intraneural application of local anesthetics may cause mechanical injury and pressure ischemia of nerve fascicles. Previous studies, however, have used small animal models and clinically irrelevant injection speed or equipment. Our hypothesis is that an intraneural injection is heralded by higher injection pressure and leads to neurologic impairment in pigs. Ten pigs of mixed breed were studied. After general anesthesia, the sciatic nerves (n = 20) were exposed bilaterally. Under direct vision, a 25-gauge insulated nerve block needle was placed either extraperineurally (n = 10) or subperineurially (n = 10), and 4 ml of preservative-free lidocaine 2% was injected using an automated infusion pump (15 ml / min). Injection pressure data were acquired using an in-line manometer coupled to a computer via an analog-to-digital conversion board. After injection, the animals were awakened and subjected to serial neurologic examinations during the 24 post-intervention hours. All but two perineural injections resulted in injection pressures below 20 psi. In contrast, intraneural injections resulted in significantly higher peak pressures. In 7 (70%) intraneural injections, the injections pressures were over 20 psi (20-50 psi). Neurologic function returned to baseline within 24 hours in all sciatic nerve receiving perineural injections. In contrast, residual neurologic impairment was present in 7 sciatic nerves after intraneural injection; residual neurologic impairment was associated with injection pressures > 20 psi. The results indicate that high injection pressure during intraneural injection may be indicative of intrafascicular injection and may predict the development of neurologic injury. Key words: nerve block, injection pressure, neurologic injury, pigs